Public Officials’ Profile and Skills in Presiding Meetings, Writing Agenda, Minutes and Resolutions - Arong, Cecilia D. (JPAIR Multidisciplinary Research, 2012)
Local legislation is effective for good governance. Legislators must be proficient in presiding meetings, drafting resolution, formulating agenda, taking down minutes and writing official communications. This study assesses public officials’ profile in presiding meetings and in writing agenda, taking down minutes and drafting resolutions. The study used the descriptive design. Fish bowl technique determines 23 Village captains, their councilors, SK chairmen, secretaries and treasurers as respondents. Results revealed that most captains and councilors are male; most secretaries and treasurers are female. Majority are 50 years and below; Most are college graduates/college level; first termer. Councilors are reelected. Majority of the secretaries and treasurers are reappointed. Majority have attended one seminar on writing agenda/resolutions. Nearly all captains and secretaries can formulate agenda while majority of the councilors and treasurers cannot. Majority of the captains, councilors, and treasurers claim they cannot take down minutes and cannot draft resolutions. The study concludes that officials lack competence in presiding meetings and writing resolutions.